2014
DOI: 10.1128/jvi.01505-14
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Specific Memory CD8 T Cells Provide Substantial Protection from Lethal Severe Acute Respiratory Syndrome Coronavirus Infection

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV IMPORTANCEVirus-specific CD8 T cells are required for pathogen clearance following primary SARS-CoV infection. However, the role of SARS-CoV-specific memory CD8 T cells in mediating protection after SARS-CoV challenge has not been previously investigated. In this study, using a prime-boost immunization approach, we showed that virus-specific CD8 T cells protect susceptible 8-to 10-month-old mice from lethal SARS-CoV challenge. Thus, future vaccines agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
431
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(457 citation statements)
references
References 51 publications
11
431
3
8
Order By: Relevance
“…Following RSV challenge, DC-LM-immunized mice exhibited significantly enhanced weight loss, pulmonary dysfunction, and mortality compared to controls. These results were unexpected given that similar immunization approaches to generate high magnitude memory CD8 T cell responses to other respiratory viruses, including influenza virus and SARS coronavirus, did not result in immunopathology following viral challenge [70,71]. Interestingly, the induction of immunopathology mediated by both primary and memory CD8 T cells is largely driven by cytokine production, particularly IFN-γ and TNF, as will be discussed in detail in Sections 3.2 and 3.3 below [12,14].…”
Section: Cd8 T Cell-mediated Immunopathologymentioning
confidence: 97%
“…Following RSV challenge, DC-LM-immunized mice exhibited significantly enhanced weight loss, pulmonary dysfunction, and mortality compared to controls. These results were unexpected given that similar immunization approaches to generate high magnitude memory CD8 T cell responses to other respiratory viruses, including influenza virus and SARS coronavirus, did not result in immunopathology following viral challenge [70,71]. Interestingly, the induction of immunopathology mediated by both primary and memory CD8 T cells is largely driven by cytokine production, particularly IFN-γ and TNF, as will be discussed in detail in Sections 3.2 and 3.3 below [12,14].…”
Section: Cd8 T Cell-mediated Immunopathologymentioning
confidence: 97%
“…However, CD4+ T cells are more susceptible to MERS‐CoV infection. The depletion of CD8+ T cells do not affect and delay viral replication at the time of infection with SARS‐CoV 77,78 . Depletion of CD4+ T cells is associated with reduced pulmonary recruitment of lymphocytes and neutralizing antibody and cytokine production, resulting in a strong immune‐mediated interstitial pneumonitis and delayed clearance of SARS‐CoV from lungs 79 .…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%
“…In contrast, virus-specific memory CD8 + T cells persisted for up to 6 years after SARS-CoV infection, at which time memory B cells and virus-specific antibodies were undetectable (Yang et al, 2006). It has been shown that memory CD8 + T cells specific for an immunodominant epitope substantially protected aged mice from lethal SARS-CoV infection (Channappanavar et al, 2014). After challenge, memory CD8 + T cells produced effector cytokines (interferon gamma, IFN-γ; tumor necrosis factor alpha, TNF-α; and interleukin 2, IL-2) and cytolytic molecules, reducing viral loads in the lung.…”
Section: Requirement Of B-and T-cell Responses For Protectionmentioning
confidence: 99%